ASYMMETRIC CONE DISTRIBUTION AND ITS CLINICAL APPEARANCE IN RETINITIS PIGMENTOSA. Issue 7 (July 2016) - Nakagawa, Satoko; Oishi, Akio; Ogino, Ken; Morooka, Satoshi; Oishi, Maho; Sugahara, Masako; Yoshimura, Nagahisa
Abstract : Purpose: To report the characteristic changes of fundus autofluorescence in the nasal retina of patients with retinitis pigmentosa. Methods: We investigated 113 eyes of 113 patients with retinitis pigmentosa. We obtained wide-field fundus autofluorescence images and evaluated the status of the retina nasal to the optic disk. The patients were divided into the following three groups: those without nasal sparing (advanced), those with nasal sparing, and those with larger intact areas in addition to the nasal retina (early). Visual acuity, visual field area, age, and the duration of the symptom were compared among the groups. Results: Twenty eyes (17.7%), 51 (45.1%), and 42 (37.1%) were classified as early, nasal sparing, and advanced, respectively. The nasal retina was essentially preserved in the early group. The clinical characteristics' analysis suggested that the disease progression appears from that represented by early groups, then nasal sparing groups, and finally advanced groups. The authors found that the nasal sparing pattern bears a close resemblance to the previously reported cone photoreceptor distribution. Conclusion: Wide-field fundus autofluorescence imaging detected nasal sparing in retinitis pigmentosa. The characteristic fundus autofluorescence pattern should reflect cone photoreceptor distribution in the human retina. This finding may be an example of the clinical appearance of asymmetric photoreceptor distribution. Abstract : Supplemental Digital Content is Available in the Text.The authors found that the fundus autofluorescence in retinitis pigmentosa patients often reveals sparing of the nasal retina. The clinical data analysis suggested that the pattern appears in the course of the disease. The findings are most likely a result of asymmetric distribution of cone photoreceptors in the human retina.